The Value of Ozone in CT-Guided Drainage of Multiloculated Pyogenic Liver Abscesses: A Randomized Controlled Study - Bing Li; Chuan Liu; Lang Wang; Yang Li; Yong Du; Chuan Zhang; Xiao-xue Xu; Han Feng Yang (Canadian Journal of Gastroenterology and Hepatology)
Objective. This study was designed to compare the effects of catheter drainage alone and combined with ozone in the management of multiloculated pyogenic liver abscess (PLA). Methods. The prospective study included 60 patients diagnosed with multiloculated PLA. All patients were randomly divided into two groups: catheter drainage alone (group I) and catheter drainage combined with ozone (group II). Drainage was considered successful when (1) the abscess cavity was drained and (2) clinical symptoms were resolved. Kruskal-Wallis nonparametric test was used to compare the success rates, length of stay (LOS), and need for further surgery of the two groups. P<0.05 indicates significant difference. Results. All patients’ catheters were successfully placed under CT guidance. Group I was treated with catheters alone and group II was treated with catheters and ozone. The success rates of groups I and II were 86% and 96%, respectively (P<0.05). And compared with group II, the duration of fever in group I was longer (P<0.05), and the LOS was also longer (P<0.05). Conclusion. Catheter drainage combined with ozone is an effective and safe treatment in multiloculated PLA. The Clinical Registration Number is ChiCTR1800014865.